2021
DOI: 10.1016/j.jseint.2021.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Inlay total shoulder arthroplasty for primary glenohumeral arthritis

Abstract: Background Anatomic total shoulder arthroplasty with a nonspherical humeral head and inlay glenoid replacement has been introduced in the past; however, clinical evidence remains limited. We hypothesized that patients with advanced glenohumeral arthritis demonstrate significant improvements in pain and function. Methods Prospective patient-reported outcomes (PROs) included the American Shoulder and Elbow Surgeons score, a pain visual analog scale, and satisfaction. Rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Five studies with a total of 133 patients (148 shoulders) met the criteria for inclusion. 17,[22][23][24][25] One of the included articles is level III evidence, 17 while the remaining four are level IV evidence. [22][23][24][25] Three are retrospective studies 17,24,25 and two are prospective studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies with a total of 133 patients (148 shoulders) met the criteria for inclusion. 17,[22][23][24][25] One of the included articles is level III evidence, 17 while the remaining four are level IV evidence. [22][23][24][25] Three are retrospective studies 17,24,25 and two are prospective studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…17,[22][23][24][25] One of the included articles is level III evidence, 17 while the remaining four are level IV evidence. [22][23][24][25] Three are retrospective studies 17,24,25 and two are prospective studies. 22,23 All articles were published between 2019 and 2022.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“… 55 , 56 Inlay TSA has successfully treated primary glenohumeral arthritis, resulting in significant functional improvement and pain relief for varying glenoid morphologies. 57 Davis et al 58 studied inset mini-glenoids in nine shoulders with severe glenoid dysplasia and medial glenoid bone loss and found that the component led to satisfactory clinical outcomes. Gunther and Tran 59 reported significant long-term clinical improvements with no loosening or revision in a study of 21 patients with severely deficient bone treated using inset glenoids.…”
Section: Inlay Glenoidsmentioning
confidence: 99%